Doing philosophy with young children: theory, practice, and resources. Issue 1 (2nd January 2022) - Kennedy, David
ABSTRACT: The last half-century has seen a slow, tentative change in adult attitudes about young children's capacity to think abstractly. Parents and teachers know the young child as a dramatic mixture of the concrete, sense-bound, and the transcendent, and it is just that mixture, cultivated and pursued, which makes for philosophy. Young children's capacity for wonder runs through all their discourse, but their speculation tends to fall on the thematic categories of appearance and reality, identity and continuity, permanence growth and transformation, 'ultimate questions' such as death and deity, and epistemological issues (how do I/you know that?). While play and story are the primary languages of early childhood, communal philosophical discussion introduces the child to a new one, which demands new skills: listening carefully to another's statement, waiting to speak, formulating a response which takes another's statement into account, staying on the subject, and giving reasons for judgements. The leader of young children's philosophical discussions is model, encourager, and sometimes enforcer of fundamental rules (not interrupting, keeping at least generally on the subject, etc.), and an interpreter of children to each other, for often a young child has a significant thought, but can communicate it only elliptically or partially. Teacher resources include, not just the stories and discussion plans of the Philosophy for Children curriculum, but numerous picture books for children that suggest philosophical concepts, as well as concrete 'object lessons' designed to spark group dialogue.